Tracking engineering education research and development: contributions from bibliometric analysis - Williams, Bill (2013)
Submitted by Cristina Manessiez (cristina.manessiez@estbarreiro.ips.pt) on 2013-05-16T15:49:00Z No. of bitstreams: 1 TrackingEngineeringEducationResearchDevelopment.pdf: 732334 bytes, checksum: c97e853fbabd489e2ecae1b76707fd9d (MD5)